2020
DOI: 10.26848/rbgf.v13.6.p2978-2991
|View full text |Cite
|
Sign up to set email alerts
|

Bioma Cerrado: fragilidades e potencialidades socioambientais de um projeto de trilha no Parque Nacional Serra da Canastra

Abstract: O ecoturismo é uma das atividades mais desenvolvidas em Parques Nacionais. A implementação de trilhas eco turísticas pode funcionar como atrativo turístico e favorecer empreendimentos locais, entretanto, podem causar impactos negativos diretos ao meio ambiente. Esses impactos podem ser minimizados através de estudos prévios para verificação de viabilidade na implementação das trilhas. Sendo assim, o objetivo deste trabalho foi apontar fragilidades e potencialidades socioambientais de um projeto de trilha para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regarding the degradation of the trails, it was possible to observe in the PNMA the occurrence of several sources/signs of it (Figure 4), by occurrence: forest fires/burnings (17.5%); irregular opening of trails/deforestation (15%); pasture, introduction of non-autochthonous species, presence of domestic animals, floral discontinuity (10% each); plant extraction, fishing and noise pollution (7.5% each); and temporary/permanent crops and mined area (2.5% each). Considering deforestation and species evasion, Marcondes et al (2020) also observed this impact on a proposed trail in the Parque Nacional da Serra da Canastra (MG). As for noise pollution, there was noise coming mainly from the surroundings, due to vehicular traffic on the access roads.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 97%
“…Regarding the degradation of the trails, it was possible to observe in the PNMA the occurrence of several sources/signs of it (Figure 4), by occurrence: forest fires/burnings (17.5%); irregular opening of trails/deforestation (15%); pasture, introduction of non-autochthonous species, presence of domestic animals, floral discontinuity (10% each); plant extraction, fishing and noise pollution (7.5% each); and temporary/permanent crops and mined area (2.5% each). Considering deforestation and species evasion, Marcondes et al (2020) also observed this impact on a proposed trail in the Parque Nacional da Serra da Canastra (MG). As for noise pollution, there was noise coming mainly from the surroundings, due to vehicular traffic on the access roads.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 97%